Reliability Analysis of Electric Power Systems Considering Cyber Security - (:unkn) unknown (My University, 2019)
The new generation of the electric power system is the modern smart grid which is essentially a cyber and physical system (CPS). Supervisory control and data acquisition (SCADA)/energy management system (EMS) is the key component of CPS, which is becoming the main target of both external and insider cyberattacks. Cybersecurity of the SCADA/EMS system is facing big challenges and influences the reliability of the electric power system. Characteristics of cyber threats will impact the system reliability. System reliability can be influenced by various cyber threats with different attack skill levels and attack paths. Additionally, the change of structure of the target system may also result in the change of the system reliability. However, very limited research is related to the reliability analysis of the electric power system considering cybersecurity issue. A large amount of mathematical methods can be used to quantify the cyber threats and simulation processes can be applied to build the reliability analysis model. For instance, to analyze the vulnerabilities of the SCADA/EMS system in the electric power system, Bayesian Networks (BNs) can be used to model the attack paths of cyberattacks on the exploited vulnerabilities. The mean time-to-compromise (MTTC) and mean time-to-failure (MTTF) based on the Common Vulnerability Scoring System (CVSS) can be applied to characterize the properties of cyberattacks. What’s more, simulation approaches like non-sequential or sequential Monte Carlo Simulation (MCS) is able to simulate the system reliability analysis and calculate the reliability indexes. In this thesis, reliability of the SCADA/EMS system in the electric power system considering different cybersecurity issues is analyzed. The Bayesian attack path models of cyberattacks on the SCADA/EMS components are built by Bayesian Networks (BNs), and cyberattacks are quantified by its mean time-to-compromise (MTTC) by applying a modified Semi-Markov Process (SMP) and MTTC models. Based on the IEEE Reliability Test System (RTS) 96, the system reliability is analyzed by calculating the electric power system reliability indexes like LOLP and EENS through MCS. What’s more, cyberattacks with different lurking strategies are considered and analyzed. According to the simulation results, it shows that the system reliability of the SCADA/EMS system in the electric power system considering cyber security is closely related to the MTTC of cyberattacks, which is influenced by the attack paths, attacking skill levels, and the complexity of the target structure. With the increase of the MTTC values of cyberattacks, LOLP values decrease, which means that the reliability of the system is better, and the system is safer. In addition, with the difficulty level of lurking strategies of cyberattacks getting higher and higher, though the LOLP values of scenarios don’t increase a lot, the EENS values of the corresponding scenarios increase dramatically, which indicates that the system reliability is more unpredictable, and the cyber security is worse. Finally, insider attacks are discussed and corresponding LOLP values and EENS values considering lurking behavior are estimated and compared. Both LOLP and EENS values dramatically increase owing to the insider attacks that result in the lower MTTCs. This indicates that insider attacks can lead to worse impact on system reliability than external cyber attacks. The results of this thesis may contribute to the establishment of perfect countermeasures against with cyber attacks on the electric power system.